Making place through urban restructuring : the case of Mthatha - Dzinotyiweyi, Gwinyai (School of Architecture, Planning and Geomatics, 2014)
This dissertation explores the notion of using design in a manner that (re)embraces and (re)amplifies the unique qualities that define the South African city, in this case – Mthatha. I emphasize "(re)" as over the last 80 years, South Africa's cities have been structured and restructured according to the dictates of the Modern Movement whose ideas are rooted in the separation of the functions of "live, work and play" (Athens Charter 1933). Its most ardent propagators also argued that humanity's habitual needs could be accommodated for through the triumphs of industry and technology. It was also held that the sensitive consideration of the unique characteristics of a particular place be consigned to the dust-bin of history. This was in favour of a universal design language that would homogenize space. These ideas arrived in South Africa almost as soon as they were formulated in Europe through the links that academic architects such as Rex Martienssen had CIAM (Parnell and Marbin 2000). The institutionalisation of apartheid in 1948 also found in Modernism the appropriate tools of separation with which to carry out its ideology spatially. My analysis and evaluation of Mthatha, presented here after 3 visits to the city, confirms that the city is currently structured and continues to grow in a manner that ignores its unique qualities giving rise to a feeling of placelessness. Moreover, the influence of global capital has facilitated its commodification in the form of shopping malls and supermarkets which negatively manipulate its local economy and exacerbate this feeling. It is within this context that I propose the restructuring of Mthatha, informed by ideas drawn from Place Theory, Contextualism and Collage City as well as Dynamic City/ Minimalism. Through these propositions, I show that it is possible to regain the qualities of a place through minimalist design interventions that clarify city structure in a manner that informs the growth of the city along a trajectory that respects and embraces that which defines its uniqueness.